2014
DOI: 10.1155/2014/642793
|View full text |Cite
|
Sign up to set email alerts
|

High-Dialysate-Glucose-Induced Oxidative Stress and Mitochondrial-Mediated Apoptosis in Human Peritoneal Mesothelial Cells

Abstract: Human peritoneal mesothelial cells (HPMCs) are a critical component of the peritoneal membrane and play a pivotal role in dialysis adequacy. Loss of HPMCs can contribute to complications in peritoneal dialysis. Compelling evidence has shown that high-dialysate glucose is a key factor causing functional changes and cell death in HPMCs. We investigated the mechanism of HPMC apoptosis induced by high-dialysate glucose, particularly the role of mitochondria in the maintenance of HPMCs. HPMCs were incubated at gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 30 publications
6
30
0
Order By: Relevance
“…There have been several studies demonstrating the role of ROS in the development of peritoneal fibrosis [35,36] . High glucose and glucose-based PD solutions induced generation of ROS in cultured HPMCs [37–39] . Furthermore, treatment with antioxidants, NAC or catalase, effectively reversed high-glucose-induced change in E-cadherin and α-SMA [35] .…”
Section: Discussionmentioning
confidence: 97%
“…There have been several studies demonstrating the role of ROS in the development of peritoneal fibrosis [35,36] . High glucose and glucose-based PD solutions induced generation of ROS in cultured HPMCs [37–39] . Furthermore, treatment with antioxidants, NAC or catalase, effectively reversed high-glucose-induced change in E-cadherin and α-SMA [35] .…”
Section: Discussionmentioning
confidence: 97%
“…Mesothelial cell injury is the first step in the development of peritoneal fibrosis, later leading to sclerosis [ 8 , 9 ], with bio-incompatibility of the PD solution and toxic molecules playing a central role in the pathology [ 10 ]. These molecules include glucose and glucose degradation products (GDPs) in the PD solution [ 11 13 ], and exogenous oxidants, such as iron [ 14 , 15 ]. Recent histological studies have reported that the use of neutral PD solutions with low GDPs are beneficial in ameliorating histological changes in the membrane [ 16 , 17 ], although the risk of EPS remains an issue of serious concern, even in patients treated with neutral PD solutions [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since high glucose is known to be able to elicit cell injury via induction of oxidative stress [19, 20], we tested whether oxidative stress was involved in PDS-induced PMC injury. Using fluorescent probes for ROS and superoxide, we detected an increased fluorescence intensity in PDS-treated cells, reflecting an elevation in ROS and superoxide production (Fig.…”
Section: Resultsmentioning
confidence: 99%